2018
DOI: 10.3390/ijerph15071438
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk among Immigrants and Ethnic Minorities: A Literature Overview

Abstract: Recent studies have demonstrated that immigrants and ethnic minorities may be at higher risk of suicidal behaviour as compared to the general population. We conducted a literature search to identify studies in English from 1980 to 2017 related to suicide risk among immigrants and ethnic minorities. Six hundred and seventy-eight reports were screened, and 43 articles were included in the qualitative synthesis of the review. Some studies reported lower rates of suicide attempts, while other findings suggested hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 71 publications
3
89
1
3
Order By: Relevance
“…to natural disasters is associated with a higher risk for serious mental illnesses, anxiety, PTSD, and depression, 2,3,5,6,[8][9][10] our study does not demonstrate this.…”
Section: Figure 1 Comparative Prevalence Of Possible Psychological DIcontrasting
confidence: 72%
“…to natural disasters is associated with a higher risk for serious mental illnesses, anxiety, PTSD, and depression, 2,3,5,6,[8][9][10] our study does not demonstrate this.…”
Section: Figure 1 Comparative Prevalence Of Possible Psychological DIcontrasting
confidence: 72%
“…This study found that the participants who could not get their medicine prescribed because they could not make appointments with the doctor skipped doses, and this negatively affected their compliance to treatment. Forte et al found that death risk was higher for refugees than locals due to high rates of suicide‐oriented behaviors and suicide. Among the reasons for this were the difficulties in accessing health services, which shows the importance of the accessibility of mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Being exposed to warfare, famine, poverty, diseases, refugee camps discrimination, and racism can be very challenging. Thus, refugees are at higher risk of posttraumatic stress disorder, depression, schizophrenia, addiction, and suicide than the general population …”
Section: Introductionmentioning
confidence: 99%
“…Inadequate interpretation may lead to serious consequences for patients with mental problems [48]. Language barriers are known to be associated with poor mental health, a low use of appropriate services, and an increase in suicide behavior [13,28,49]. The present study revealed that the use of medical interpreters remains rare, and this limitation may impede the health conditions, especially the mental health conditions, of foreign residents.…”
Section: Pathways To Hospital Visitation and Language Problemsmentioning
confidence: 70%